2005
DOI: 10.1108/09513550510608886
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the research‐practice gap: barriers and facilitators to research use among school principals from England and Israel

Abstract: When a professional practitioner is faced with making a decision about what to do in a particular situation, do they base that decision on findings from research? This paper reports on qualitative and quantitative research which examined school principals' perceptions of barriers to the use of research. To facilitate a comparison the study was conducted simultaneously in two countries: England and Israel using interviews, focus groups and the Barriers Scale survey instrument (Funk et al., 1991).The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 73 publications
(127 reference statements)
1
11
0
Order By: Relevance
“…According to the results of present research, in terms of the individual restraining factors, lack of time due to job preoccupation has had the highest frequency in view of professors; this is consistent with results of the study of Tan M et al, Hemsley-Brown J et al and Roxburgh M. [20][21][22] This individual barrier can be caused by the multiple responsibilities of professors in the training, consulting, and executive and administrative areas in university environments. Engaging in executive and administrative activities, in addition to take a lot of valuable time of faculty members who can be spent on research and science production, has also this threat as a consequence that being continuous of staying in such posts creates gradually a kind of administrative tendency and routine in these individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results of present research, in terms of the individual restraining factors, lack of time due to job preoccupation has had the highest frequency in view of professors; this is consistent with results of the study of Tan M et al, Hemsley-Brown J et al and Roxburgh M. [20][21][22] This individual barrier can be caused by the multiple responsibilities of professors in the training, consulting, and executive and administrative areas in university environments. Engaging in executive and administrative activities, in addition to take a lot of valuable time of faculty members who can be spent on research and science production, has also this threat as a consequence that being continuous of staying in such posts creates gradually a kind of administrative tendency and routine in these individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Also in his study Hemsley-Brown J has reported the lack of databases as one of the strategic restraining factors in order to carry out research. 21 To adjust this barrier, the preparation of research possibilities and facilities, providing the valid scientific resources, the creation of internally information databases relating to conducted or running researches are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Students of Ardabil University of Medical Sciences in Iran rated the lack of access to information sources as the highest mean score barrier in research productivity. Another study reported the lack of access to databases as a significant barrier to research (Hemsley-Brown & Oplatka, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors (Kirst, 2000;Hemsley-Brown and Oplatka, 2005) search for the reasons for this gap among representatives of agricultural practice. These include conservatism and distrust to implement new knowledge, low competences and poor perception.…”
Section: Knowledge Transfer Process -Application Of Research In Practicementioning
confidence: 99%
“…Many advisors perceive scientists as those who belong to the world of theory, which is distant from the problems of agricultural practice, which are not undertaken by them. It is very important to try more strictly to link the worlds of science with agricultural practice to level the existing gap in the knowledge of transfer system by creating better atmosphere of cooperation and new relations (Hemsley-Brown and Oplatka, 2005).…”
Section: Knowledge Transfer Process -Application Of Research In Practicementioning
confidence: 99%